HUBUNGAN ASUPAN ZAT BESI, PROTEIN, VITAMIN C DAN POLA MENSTRUASI DENGAN KADAR HEMOGLOBIN PADA REMAJA PUTRI DI SMAN 1 MANYAR GRESIK[Correlation Between Intake of Iron, Protein, Vitamin C and Menstruation Pattern with Haemoglobin Concentration among Adolescent Girl in Senior High School 1 Manyar Gresik] - Cynthia Almaratus Sholicha; Lailatul Muniroh (Universitas Airlangga, 2019)
One of nutrition problem that needs to get high attention is anemia. Anemia is a condition that develops when healthy red blood cells below normal. Inadequate intake of nutrient, menstruation, infectious diseases, and lack of knowledge can caused anemia. Monthly menstruation and growth period drive adolescent girls pronen to anemia. The purpose of this study was to analyze correlation between intake of iron, protein, vitamin C and menstruation patterns with anemia among adolescent girls. This study used cross sectional design. Population of this study was adolescent student grade X and XI at SMAN 1 Manyar Gresik. Sixty two students were selected using proportional random sampling . Data were collected with semi quantitative food frequency questionnaire, structured questionnaire, and digital haemoglobinmeter. Data were analyzed using Spearman correlation test and Chi-square test. Results showed intake of iron (r=0.635; p=0.000), protein (r=0.663; p=0.000), and vitamin C (r=0.780; p=0.000) was correlated with haemoglobin concentration similiar with menstruation pattern which also had signifi cant correlation with anemia (p=0.002). Lower intake of iron, protein and vitamin C, caused lower haemoglobin concentration. Thus, anemia incidence will be higher. Adolescent girl are expected to increase food consumption of food source of iron and consume iron supplement routinely to replace iron that lost during menstruation.